Care management instruments used by nurses in the emergency hospital services - Rabelo,Simone Kroll (2021)
ABSTRACT Objective: To describe the instruments used by nurses for the management of care in face of the demands of the emergency hospital service. Method: This is a qualitative study, with triangulation of data from interviews, focus groups, and documents, conducted with nurses from an Emergency Hospital Service in a state in southern Brazil. Data were subjected to thematic content analysis. Results: Seventeen nurses participated in the study. The categories emerging from this study were view of the whole picture, definition of priorities, and physical instruments. These instruments are used by nurses to manage multiple tasks and provide adequate care to patients with different levels of complexity, in the face of an intense and unpredictable work process due to the constant demand for care. Conclusion: The instruments used by nurses in their work process are mainly skills and attitudes developed as a coping strategy at an intense and complex work environment.